Quantifying Access to Speech in Children with Hearing Loss: The Influence of the Work of Pat Stelmachowicz on Measures of Audibility - Wiseman, Kathryn B.; McCreery, Ryan W. (Seminars in Hearing, 2023)
This article reviews the research of Pat Stelmachowicz on traditional and novel measures for quantifying speech audibility (i.e., pure-tone average [PTA], the articulation/audibility index [AI], the speech intelligibility index, and auditory dosage) as predictors of speech perception and language outcomes in children. We discuss the limitations of using audiometric PTA as a predictor of perceptual outcomes in children and how Pat's research shed light on the importance of measures that characterize high-frequency audibility. We also discuss the AI, Pat's work on the calculation of the AI as a hearing aid outcome measure, and how this work led to the application of the speech intelligibility index as a clinically utilized measure of unaided and aided audibility. Finally, we describe a novel measure of audibility—auditory dosage—that was developed based on Pat's work on audibility and hearing aid use for children who are hard of hearing.
Keywords: audibility; hard of hearing; speech recognition; articulation index; speech intelligibility index; auditory dosage; pure-tone average